(x-1)/2 - (3x-2)/4 = 2
2(x-1)-(3x-2)=8
2x-2-3x+2=8
x=-8
(2x-1)/10 - x/4 = 1 - (3x+1)/8
8x-4-10x=40-15x-5
-2x-4=-15x+35
13x=39
x=3
2/3 - (x-1)/6 + (4-3x)/9 = (x-5)/2
12-3x+3+8-6x=9x-45
-9x+23=9x-45
18x=68
x=68/18
x=34/9
2*(2x-1)/3 - (x-5) = x/8 + (x+7)/6
16(2x-1) - 24(x-5) =3x + 4(x+7)
32x-16 - 24x+120 =3x + 4x+28
8x+104=7x+28
x=-76
-2/3 = (4x-1)/6 + 1/4 (x+1) -2
-8=8x-2+3x+3-24
-8=11x-23
11x=15
x=15/11
(m-1)x-2(x-3)=x+m
m=-3
(-3-1)x-2(x-3)=x-3
-4x-2x+6=x-3
7x=9
x=9/7
(m-1)x-2(x-3)=x+m
x=2
(m-1)2-2(2-3)=2+m
2m-2+2=2+m
m=2
(m-1)x-2(x-3)=x+m
mx-x-2x+6=x+m
mx-4x=m-6
x(m-4)=m-6
x=(m-6)/(m-4)
pentru m=4
(4-1)x-2(x-3)=x+4
3x-2x+6=x+4
x+6=x+4
6=4
deci nu avem solutii